Conductive coating as well as preparation method and application thereof
By modifying the graphene and carbon nanotubes, high dispersion and high stability carbon nanotubes/graphene conductive paste are prepared, which solves the problems of uneven conductivity and poor stability of existing conductive coatings when used on the aircraft surface, and realizes the preparation and application of conductive coatings with high storage stability.
Patent Information
- Application Number
- CN202510391460.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
When used on the surface of an aircraft, existing conductive coatings have problems such as uneven conductivity, poor stability and easy breakdown, which is difficult to meet the antistatic and mechanical performance requirements in high altitude environments of the aircraft.
By modifying the graphene and carbon nanotubes, a high dispersion and high stability carbon nanotube/graphene conductive paste is prepared, and a high storage stability conductive coating is prepared in combination with components such as fluorocarbon resin.
The high dispersion, good conductivity and long-term storage stability of conductive coatings are achieved, which reduces flight resistance and improves the overall performance of the coating.
Smart Images

Figure CN119899559A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coating technology, and more particularly to a conductive coating containing carbon nanotube / graphene conductive slurry, a preparation method and application thereof, and more particularly to a conductive coating with high storage stability, a preparation method and application thereof. Background Art
[0002] When an aircraft flies at high speed in a complex high-altitude environment, its surface will generate strong friction with the air, causing static electricity. If the static electricity cannot be released in a timely and effective manner, it will interfere with the aircraft's electronic equipment and seriously affect the normal operation of the aircraft. Therefore, the aircraft surface needs to be coated with antistatic coatings, and it needs to have conductive functions and good mechanical properties. Most of the commonly used conductive coatings on the market currently add conductive fillers to the coating, such as carbon black, conductive fibers, conductive mica powder, etc. Although conductive fibers have good conductive properties, their resistance value control ability is poor, and they are easily broken down and cause harm. In addition, they have poor dispersibility, resulting in uneven distribution of coating resistance values, and cannot be used in aircraft conductive coatings.
[0003] Carbon nanotubes are a tubular structure composed of carbon atoms. They are an isotope isomer of crystalline carbon. They are light in weight, have perfectly connected hexagonal structures, and have many unusual mechanical, electrical, and chemical properties. Their resistance is independent of their length and diameter. When electrons pass through carbon nanotubes, they do not generate heat. Therefore, the transmission of electrons in carbon nanotubes is like the transmission of light signals in optical fiber cables. The energy loss is small, and they are excellent conductive materials. Graphene is a single atomic layer of graphite with a two-dimensional honeycomb crystal structure composed of closely packed sp2 hybridized carbon atoms. It has excellent optical, mechanical, electrical, and thermal properties, and has a large specific surface area and impermeability. It has a very obvious advantage in electrical conductivity. Although carbon nanotubes and graphene are both good conductive materials, they have poor dispersion and unqualified stability when used alone, resulting in a lack of practical research in the current market.
[0004] Invention patent CN116023846A proposes a carbon nanotube-containing electrostatic conductive coating and its preparation method. The patent modifies carbon nanotubes to enhance the conductivity of the coating, but carbon nanotubes have high viscosity and are difficult to disperse. The patent does not involve a discussion of dispersants. Invention patent CN116731593A proposes a graphene electrostatic conductive coating and its preparation method. The patent uses a phenolic epoxy resin system to improve the corrosion resistance of the coating, but its weather resistance needs to be improved compared to fluorocarbon resin. Summary of the invention
[0005] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.
[0006] The present application modifies the dispersant in the graphene / carbon nanotube conductive slurry, greatly improving the dispersion effect, overcoming the defects of carbon nanotubes and graphene themselves, solving the problem of poor dispersibility caused by the agglomeration of carbon nanotubes, and improving storage stability, thereby preparing a conductive coating with high storage stability, and the coating has a low surface density, which greatly reduces the flight resistance during the flight of the aircraft. Therefore, the present application provides a conductive coating with good dispersibility, good conductivity, and good storage stability. The conductive coating with high storage stability prepared by the present application has taken an important step in the use of conductive coatings for aircraft.
[0007] The first aspect of the present application provides a conductive coating, which consists of component A, component B and component C, wherein, in parts by weight, component A is 100 parts, component B is 8-12 parts, and component C is 10-25 parts.
[0008] In an exemplary embodiment, the component A includes, by weight: 20-45 parts of fluorocarbon resin, 10-30 parts of filler, 5-17 parts of pigment, 3-7 parts of carbon nanotube / graphene conductive paste, 2-6 parts of auxiliary agent, 10-20 parts of first diluent and 1-2 parts of matting powder; The component B: 8-12 parts of curing agent; The component C includes 10-25 parts of the second diluent.
[0009] In an exemplary embodiment, the component A may further include other additives known in the art.
[0010] In an exemplary embodiment, the component A is composed of 20-45 parts of fluorocarbon resin, 10-30 parts of filler, 5-17 parts of pigment, 3-7 parts of carbon nanotube / graphene conductive paste, 2-6 parts of auxiliary agent, 10-20 parts of first diluent and 1-2 parts of matting powder, by weight.
[0011] In an exemplary embodiment, the carbon nanotube / graphene conductive slurry is composed of the following components by weight: 0.15-0.6 parts of graphene, 0.1-0.6 parts of carbon nanotubes, 0.4-0.7 parts of positioning agent, 0.3-0.8 parts of modified dispersant and 2.5-4 parts of third diluent, wherein the weight ratio of graphene to carbon nanotubes is 3:2.
[0012] In an exemplary embodiment, in the carbon nanotube / graphene conductive paste, the weight ratio of the carbon nanotube / graphene composite in the carbon nanotube / graphene conductive paste is 7-16%. At this time, the carbon nanotube / graphene composite has good dispersibility and good storage stability.
[0013] In an exemplary embodiment, in order to further improve the anti-flocculation effect of the dispersant, the modified dispersant is a dispersant modified by a modified compound to improve the adsorption of the dispersant on the surface of the solid nanoparticles, enhance the wetting efficiency, and thus shorten the grinding time; Optionally, the modifying compound is imidazole or polyethylene glycol, preferably, imidazole; Optionally, the molar ratio of the active group of the dispersant to the modifying compound is from 1:1 to 1:2.
[0014] In an exemplary embodiment, the carbon nanotube / graphene conductive paste is composed of the following components by weight: 0.3 parts of graphene, 0.2 parts of carbon nanotubes, 0.5 parts of modified dispersant, 0.5 parts of positioning agent, and 3 parts of third diluent, wherein the graphene and carbon nanotubes are mixed in a weight ratio of 3:2; or The carbon nanotube / graphene conductive slurry is composed of the following components by weight: 0.6 parts of graphene, 0.4 parts of carbon nanotubes, 0.8 parts of modified dispersant, 0.7 parts of positioning agent, and a third diluent, wherein the graphene and the carbon nanotubes are mixed in a weight ratio of 3:2; or The carbon nanotube / graphene conductive slurry is composed of the following components by weight: 0.15 parts of graphene, 0.1 parts of carbon nanotubes, 0.3 parts of modified dispersant, 0.4 parts of positioning agent, and 2.5 parts of third diluent, wherein the graphene and carbon nanotubes are mixed in a weight ratio of 3:2.
[0015] In an exemplary embodiment, in the carbon nanotube / graphene conductive paste, the positioning agent is a cellulose ester positioning agent, preferably butyl acetate cellulose.
[0016] In an exemplary embodiment, in the carbon nanotube / graphene conductive paste, the modified dispersant is a modified polymer dispersant; the polymer dispersant is selected from, for example, one or both of EFKA-4080 and BYK-220.
[0017] In an exemplary embodiment, the fluorocarbon resin is chlorotrifluoroethylene-vinyl ester resin.
[0018] In an exemplary embodiment, the fluorocarbon resin is selected from at least one of JF-2X, JF-3, ZB-F100, and ZB-F200; preferably, JF-2X.
[0019] In an exemplary embodiment, the filler is an inorganic filler, optionally selected from at least one of talcum powder, precipitated barium sulfate, and light calcium carbonate. The filler can reduce the friction coefficient and act as a lubricant.
[0020] In an exemplary embodiment, the particle size of the talc is 1250 mesh.
[0021] In an exemplary embodiment, the pigment is at least one of an organic pigment and an inorganic pigment; the color can be adjusted to red, blue, black or yellow, etc. as needed; preferably, the pigment is at least one of iron red, phthalocyanine blue, carbon black, chrome yellow, and titanium dioxide.
[0022] In an exemplary embodiment, the auxiliary agent is at least one of a leveling agent, a drying agent and an adhesion promoter.
[0023] In an exemplary embodiment, the leveling agent is selected from at least one of BYK-358, L-1984N, and BYK-361N, and the leveling agent has the effects of leveling and improving shrinkage cavities.
[0024] In an exemplary embodiment, the drying agent is dibutyltin dilaurate; preferably, dibutyltin dilaurate diluted with xylene; more preferably, 1 wt % dibutyltin dilaurate diluted with xylene. The drying agent can accelerate the curing reaction of monomers and polymers in the coating.
[0025] In an exemplary embodiment, the adhesion promoter is selected from at least one of EDL-809 and EDL-6026F, and the adhesion promoter can improve the adhesion performance between the coating and the substrate.
[0026] In an exemplary embodiment, the curing agent is an isocyanate; preferably, it is an aliphatic polyisocyanate, for example, at least one of HT-90B and N3390; more preferably, it is hexamethylene diisocyanate.
[0027] In an exemplary embodiment, the matting powder is ED-30.
[0028] In an exemplary embodiment, the first diluent, the second diluent and the third diluent respectively include at least one of cyclohexanone, propylene glycol methyl ether acetate, xylene, butyl acetate and dibasic acid ester.
[0029] In an exemplary embodiment, the compositions of the first diluent, the second diluent and the third diluent may be the same or different; preferably, the compositions of the first diluent, the second diluent and the third diluent are different.
[0030] In an exemplary embodiment, the first diluent consists of cyclohexanone and xylene in a weight ratio of (1.0-2.0):(10-20).
[0031] In an exemplary embodiment, the second diluent is composed of cyclohexanone, propylene glycol methyl ether acetate, xylene, butyl acetate and dibasic acid ester in a weight ratio of (1-2):(1-3):(20-30):(2-4):(4-8).
[0032] In an exemplary embodiment, the third diluent is composed of cyclohexanone, butyl ester, and dibasic acid ester in a weight ratio of (0.5-1):(2-2.5):(1-2).
[0033] In an exemplary embodiment, the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin, 19 parts of filler, 15 parts of pigment, 4.5 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder, 5.5 parts of additives, 16 parts of the first diluent, Component B: 10 parts of curing agent, Component C: 23 parts of the second diluent; Among them, the weight ratio of component A, component B and component C is 100:10:23.
[0034] In an exemplary embodiment, the conductive coating is composed of the following components in parts by weight: Component A: 40 parts of fluorocarbon resin, 21 parts of filler, 12 parts of pigment, 6.5 parts of carbon nanotube / graphene conductive paste, 1.5 parts of matting powder, 5.5 parts of additives, 13.5 parts of the first diluent, Component B: 10 parts of curing agent, Component C: 23 parts of the second diluent; Among them, the weight ratio of component A, component B and component C is 100:10:23.
[0035] In an exemplary embodiment, the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin, 20 parts of filler, 16.5 parts of pigment, 3.45 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder, 5.5 parts of additives, 14.55 parts of the first diluent, Component B: 10 parts of curing agent, Component C: 23 parts of the second diluent; Among them, the weight ratio of component A, component B and component C is 100:10:23.
[0036] The second aspect of the present application provides a method for preparing the above-mentioned conductive coating, the method comprising the following steps: Step 1: blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent under ultrasonic dispersion and high-speed stirring conditions to prepare a stable carbon nanotube / graphene conductive slurry; Step 2: blending the carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, first diluent and matting powder under ultrasonic dispersion and high-speed stirring conditions, and grinding the blended mixture to obtain component A; Step 3: Add the curing agent of component B and the second diluent of component C to component A and stir to obtain a conductive coating with high storage stability.
[0037] In an exemplary embodiment, step one also includes a modification treatment of the dispersant: dissolving the dispersant with a solvent, adding a modifying compound and stirring until completely dissolved; heating the reaction system and reacting under nitrogen protection; after the reaction is completed, removing the solvent to obtain a modified dispersant.
[0038] In an exemplary embodiment, in the modification process, the solvent is tetrahydrofuran.
[0039] In an exemplary embodiment, in the modification treatment, the molar ratio of the active group of the dispersant to the modifying compound is 1:1 to 1:2.
[0040] In an exemplary embodiment, during the modification process, the heating temperature is 60-80°C.
[0041] In an exemplary embodiment, in the modification treatment, the reaction time is 6-10 hours; preferably, 8 hours.
[0042] In an exemplary embodiment, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, wherein: Optionally, the power of the ultrasonic disperser is 800W; Optionally, the ultrasonic dispersion time is 5-30 min; Optionally, the temperature during ultrasonic dispersion does not exceed 30°C, because the slurry tends to agglomerate when the temperature exceeds 30°C.
[0043] In an exemplary embodiment, in step 1 and step 2, the rotation speed of the high-speed stirring is 1000 rad / min-1200 rad / min.
[0044] In an exemplary embodiment, in step 1 and step 2, the time of high-speed stirring is 1-3 hours.
[0045] In an exemplary embodiment, in step 2, the blended mixture is ground to a fineness within 25 μm; In an exemplary embodiment, in step 2, the grinding time is 1-2 hours.
[0046] In an exemplary embodiment, in step three, the stirring time is 0.2-1 h, preferably, the stirring time is 0.5 h.
[0047] The third aspect of the present application provides a conductive coating prepared by the above method.
[0048] A fourth aspect of the present application provides an application of the above-mentioned conductive coating on the surface of an aircraft.
[0049] In one exemplary embodiment, the conductive coating may be used as a primer or a topcoat.
[0050] A fifth aspect of the present application provides a coating formed by the above-mentioned conductive coating, wherein the coating is formed by applying the conductive coating onto a substrate and curing it.
[0051] In one exemplary embodiment, the substrate is an aircraft surface.
[0052] The beneficial effects of this application are embodied in: 1. In the present application, carbon nanotubes and graphene are compounded to prepare a carbon nanotube / graphene conductive paste, which overcomes the defects of carbon nanotubes and graphene themselves, solves the problem of poor dispersibility caused by the agglomeration state of carbon nanotubes, improves storage stability, and thus prepares a conductive coating with high storage stability.
[0053] 2. The conductive coating prepared in this application has good conductivity (i.e., surface resistance ≤ 10 6 Ω / sq) and three-proof properties, and has excellent bonding with the substrate and matching primer.
[0054] 3. The dispersant of the present application is modified to have a better dispersion effect in graphene carbon nanotubes, thereby enhancing the conductive path between graphene and carbon nanotubes and making the conductive performance of the coating stronger.
[0055] 4. This application optimizes the graphene and carbon nanotube compounding process in the process of preparing a conductive coating with high storage stability, adds a quantitative polymer dispersant, forms an adsorption layer on the surface of solid particles, increases the charge on the surface of the solid particles, improves the reaction force between particles that form steric hindrance, and allows the filler to be stably dispersed in the system. In the case of low viscosity, the conductive coating can be evenly coated, effectively improving the stability of the conductive coating, and increasing the viscosity without affecting the coating effect. This application takes into account the advantages of low viscosity and high dispersibility of the conductive coating, has the characteristics of convenient and simple construction, reduces processing costs, and ensures the high stability of the product. It is a technical solution that can be actually applied in industry.
[0056] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.
[0058] Figure 1 The initial particle size distribution diagram of the coating obtained by using different dispersants; Figure 2 This is the particle size distribution diagram of the coating obtained using different dispersants after 30 days of hot storage experiment. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application will be described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.
[0060] The present invention is further described in detail below in conjunction with specific examples, but the examples should not be construed as limiting the present invention. The raw materials of this application are all conventional products on the market.
[0061] Example 1 This embodiment provides a conductive coating and a preparation method thereof. The conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 11 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 1 part of carbon black, 4.5 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-809, 1.5 parts of leveling agent BYK-358, 2 parts of dibutyltin dilaurate diluted with 1%wt xylene as drying agent, 16 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene) Component B: 10 parts of isocyanate curing agent HT-90B, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 22 parts of xylene, 2.3 parts of butyl acetate, 4 parts of diformate).
[0062] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.3 parts of graphene, 0.2 parts of carbon nanotubes, 0.5 parts of modified polymer dispersant BYK161, 0.5 parts of positioning agent butyl acetate cellulose, 3 parts of the third diluent (0.5 parts of cyclohexanone, 2 parts of butyl acetate, 1 part of diformate), and the graphene and carbon nanotubes are mixed in a weight ratio of 3:2.
[0063] The mass ratio of component A to component B is 100:10.
[0064] The preparation of the conductive coating comprises the following steps: Step 1: dissolve the dispersant completely with tetrahydrofuran, add imidazole and stir until completely dissolved, wherein the molar ratio of the active group of the dispersant to the imidazole is 1:1; heat the reaction system to 60°C and react for 8 hours under nitrogen protection; after the reaction is completed, remove the solvent by rotary evaporation to obtain a modified dispersant; Under ultrasonic dispersion and high-speed stirring conditions, the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent are blended to prepare a stable carbon nanotube / graphene conductive slurry; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, first diluent and matting powder are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed by an ultrasonic disperser, the power of the ultrasonic disperser is 800W, the ultrasonic dispersion is performed for 30min, the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1 hour until the scraper fineness is controlled within 25µm to obtain component A; Step 3: Add the isocyanate curing agent of component B and the second diluent of component C to component A and stir for half an hour to obtain a conductive coating with high storage stability.
[0065] Example 2 This embodiment provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 40 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 4 parts of light calcium carbonate, 10 parts of titanium dioxide, 2 parts of 103 chrome yellow, 6.5 parts of carbon nanotube / graphene conductive paste, 1.5 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-809, 1.5 parts of leveling agent L-1984N, 2 parts of dibutyltin dilaurate diluted with 1%wt xylene as drying agent, 13.5 parts of the first diluent (1.1 parts of cyclohexanone, 13 parts of xylene), Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1 part of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 25 parts of xylene, 3 parts of butyl acetate, 6 parts of diformate).
[0066] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.6 parts of graphene, 0.4 parts of carbon nanotubes, 0.8 parts of modified polymer dispersant BYK161, 0.7 parts of positioning agent butyl acetate cellulose, 4 parts of the third diluent (0.5 parts of cyclohexanone, 2 parts of butyl acetate, 1 part of diformate), and the graphene and carbon nanotubes are mixed in a weight ratio of 3:2.
[0067] The mass ratio of component A to component B is 100:10.
[0068] The preparation of the conductive coating with high storage stability comprises the following steps: Step 1: dissolve the dispersant completely with tetrahydrofuran, add imidazole and stir until completely dissolved, wherein the molar ratio of the active group of the dispersant to the imidazole is 1:2; heat the reaction system to 80°C and react for 8 hours under nitrogen protection; after the reaction is completed, remove the solvent by rotary evaporation to obtain a modified dispersant; Under ultrasonic dispersion and high-speed stirring conditions, the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent are blended to prepare a stable carbon nanotube / graphene conductive slurry; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, first diluent and matting powder are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed by an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1 hour until the scraper fineness is controlled within 25µm, to obtain component A; Step 3: Add the isocyanate curing agent of component B and the second diluent of component C to component A and stir for half an hour to obtain a conductive coating with high storage stability.
[0069] Example 3 This embodiment provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 2 parts of iron red, 0.5 parts of phthalocyanine blue, 3.45 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-6026F, 1.5 parts of leveling agent BYK-361N, 2 parts of drying agent dibutyltin dilaurate, 14.55 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 23 parts of xylene, 3 parts of butyl acetate, 5 parts of diformate).
[0070] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.15 parts of graphene, 0.1 parts of carbon nanotubes, 0.3 parts of modified polymer dispersant Anti-Terra-203, 0.4 parts of positioning agent butyl acetate cellulose, and 2.5 parts of a third diluent (0.8 parts of cyclohexanone, 2.5 parts of butyl acetate, and 1 part of diformate); wherein the graphene and the carbon nanotubes are mixed in a weight ratio of 3:2.
[0071] The mass ratio of component A to component B is 100:10.
[0072] Step 1: dissolve the dispersant completely with tetrahydrofuran, add imidazole and stir until completely dissolved, wherein the molar ratio of the active group of the dispersant to the imidazole is 1:1; heat the reaction system to 70°C and react for 8 hours under nitrogen protection; after the reaction is completed, remove the solvent by rotary evaporation to obtain a modified dispersant; Under ultrasonic dispersion and high-speed stirring conditions, the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent are blended to prepare a stable carbon nanotube / graphene conductive slurry; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1.5 hours until the scraper fineness is controlled within 25µm, to obtain component A; Step 3: Add the isocyanate curing agent of component B and the second diluent of component C to component A and stir for half an hour to obtain a conductive coating with high storage stability.
[0073] The conductive coatings prepared in Examples 1-3 of the present application can also have good conductivity (i.e., surface resistance ≤ 10 6 Ω / sq), three-proof properties, and excellent bonding with substrates and matching primers.
[0074] Comparative Example 1 The difference from Example 1 is that single graphene is used to replace the carbon nanotube / graphene conductive paste.
[0075] Comparative Example 2 The difference from Example 1 is that a single carbon nanotube is used to replace the carbon nanotube / graphene conductive paste.
[0076] Comparative Example 3 This comparative example provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 11 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 1 part of carbon black, 4.5 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-809, 1.5 parts of leveling agent BYK-358, 2 parts of dibutyltin dilaurate diluted with 1%wt xylene as drying agent, 16 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene), Component B: 10 parts of isocyanate curing agent HT-90B, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 22 parts of xylene, 2.3 parts of butyl acetate, 4 parts of diformate).
[0077] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.3 parts of graphene, 0.2 parts of carbon nanotubes, 0.5 parts of modified polymer dispersant BYK161, 0.5 parts of positioning agent butyl acetate cellulose, 3 parts of the third diluent (0.5 parts of cyclohexanone, 2 parts of butyl acetate, 1 part of diformate), and the graphene and carbon nanotubes are mixed in a weight ratio of 3:2.
[0078] The mass ratio of component A to component B is 100:10.
[0079] The preparation of the conductive coating comprises the following steps: Step 1: Blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent to prepare a stable carbon nanotube / graphene conductive slurry; wherein the modification step of the dispersant is the same as that of Example 1; Step 2: Blending carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent to prepare component A, grinding the blended mixture for 1 hour until the scraper fineness is controlled within 25µm, to obtain component A; Step 3: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0080] Comparative Example 4 This comparative example provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 40 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 4 parts of light calcium carbonate, 10 parts of titanium dioxide, 2 parts of 103 chrome yellow, 6.7 parts of carbon nanotube / graphene conductive paste, 1.5 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-809, 1.5 parts of leveling agent L-1984N, 2 parts of dibutyltin dilaurate diluted with 1%wt xylene as drying agent, 13.3 parts of the first diluent (1.1 parts of cyclohexanone, 13 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1 part of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 25 parts of xylene, 3 parts of butyl acetate, 6 parts of diformate).
[0081] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.6 parts of graphene, 0.6 parts of carbon nanotubes, 0.8 parts of modified polymer dispersant BYK161, 0.7 parts of positioning agent butyl acetate cellulose, 4 parts of the third diluent (0.5 parts of cyclohexanone, 2 parts of butyl acetate, 1 part of diformate), and the graphene and carbon nanotubes are mixed in a weight ratio of 1:1.
[0082] The mass ratio of component A to component B is 100:10.
[0083] The preparation of the conductive coating comprises the following steps: Step 1: blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent under ultrasonic dispersion and high-speed stirring conditions to prepare a stable carbon nanotube / graphene conductive slurry; wherein the modification step of the dispersant is the same as that of Example 2; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1.5 hours until the scraper fineness is controlled within 25µm; Step 3: Add the isocyanate curing agent of component B and the second diluent of component C to component A and stir for half an hour to obtain a conductive coating with high storage stability.
[0084] Comparative Example 5 This comparative example provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 40 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 4 parts of light calcium carbonate, 10 parts of titanium dioxide, 2 parts of 103 chrome yellow, 6.5 parts of carbon nanotube / graphene conductive paste, 1.5 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-809, 1.5 parts of leveling agent L-1984N, 2 parts of dibutyltin dilaurate diluted with 1%wt xylene as drying agent, 13.5 parts of the first diluent (1.1 parts of cyclohexanone, 13 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1 part of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 25 parts of xylene, 3 parts of butyl acetate, 6 parts of diformate).
[0085] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.4 parts of graphene, 0.6 parts of carbon nanotubes, 0.8 parts of modified polymer dispersant BYK161, 0.7 parts of positioning agent butyl acetate cellulose, 4 parts of the third diluent (0.5 parts of cyclohexanone, 2 parts of butyl acetate, 1 part of diformate), and the graphene and carbon nanotubes are mixed in a weight ratio of 2:3.
[0086] The mass ratio of component A to component B is 100:10.
[0087] The preparation of the conductive coating comprises the following steps: Step 1: blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent under ultrasonic dispersion and high-speed stirring conditions to prepare a stable carbon nanotube / graphene conductive slurry; wherein the modification step of the dispersant is the same as that of Example 2; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1.5 hours until the scraper fineness is controlled within 25µm; Step 3: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0088] Comparative Example 6 This comparative example provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 40 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 4 parts of light calcium carbonate, 10 parts of titanium dioxide, 2 parts of 103 chrome yellow, 6.5 parts of carbon nanotube / graphene conductive paste, 1.5 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-809, 1.5 parts of leveling agent L-1984N, 2 parts of dibutyltin dilaurate diluted with 1%wt xylene as drying agent, 13.5 parts of the first diluent (1.1 parts of cyclohexanone, 13 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1 part of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 25 parts of xylene, 3 parts of butyl acetate, 6 parts of diformate).
[0089] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.6 parts of graphene, 0.4 parts of carbon nanotubes, 0.8 parts of modified amine salt ionic dispersant sn-5027, 0.7 parts of positioning agent butyl acetate cellulose, 3 parts of the third diluent (0.5 parts of cyclohexanone, 2 parts of butyl acetate, 1 part of diformate), and the graphene and carbon nanotubes are mixed in a weight ratio of 3:2.
[0090] The mass ratio of component A to component B is 100:10.
[0091] The preparation of the conductive coating comprises the following steps: Step 1: blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent under ultrasonic dispersion and high-speed stirring conditions to prepare a stable carbon nanotube / graphene conductive slurry; wherein the modification step of the dispersant is the same as that of Example 2; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1.5 hours until the scraper fineness is controlled within 25µm; Step 3: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0092] Comparative Example 7 The present invention provides a conductive coating and a preparation method thereof, which comprises the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 2 parts of iron red, 0.5 parts of phthalocyanine blue, 3.45 parts of conductive paste, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-6026F, 1.5 parts of leveling agent BYK-361N, 2 parts of drying agent dibutyltin dilaurate, 14.55 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 23 parts of xylene, 3 parts of butyl acetate, 5 parts of diformate).
[0093] The conductive paste is composed of the following components: 0.25 parts of nano antimony-doped tin dioxide, 0.3 parts of modified polymer dispersant Anti-Terra-203, 0.4 parts of positioning agent butyl acetate cellulose, and 2.5 parts of the third diluent (0.8 parts of cyclohexanone, 2.5 parts of butyl acetate, and 1 part of diformate).
[0094] The preparation of the conductive coating comprises the following steps: Step 1: Under ultrasonic dispersion and high-speed stirring conditions, nano antimony-doped tin dioxide, modified dispersant, positioning agent, fluorocarbon resin, filler, pigment, additive, matting powder and first diluent are blended to prepare component A; wherein the modification step of the dispersant is the same as that of Example 3; ultrasonic dispersion is performed using an ultrasonic disperser, the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, the temperature is controlled within 30°C during the entire ultrasonic dispersion process, the speed of high-speed stirring is controlled at 1200 rad / min, the blended mixture is ground for 1.5 hours, and the scraper fineness is controlled within 25µm; Step 2: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0095] Comparative Example 8 This comparative example provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 2 parts of iron red, 0.5 parts of phthalocyanine blue, 3.45 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-6026F, 1.5 parts of leveling agent BYK-361N, 2 parts of drying agent dibutyltin dilaurate, 14.55 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 23 parts of xylene, 3 parts of butyl acetate, 5 parts of diformate).
[0096] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.15 parts of graphene, 0.1 parts of carbon nanotubes, 0.3 parts of modified controlled radical dispersant DISUPER S9100, 0.4 parts of positioning agent butyl acetate cellulose, and 2.5 parts of a third diluent (0.8 parts of cyclohexanone, 2.5 parts of butyl acetate, and 1 part of diformate); wherein the graphene and the carbon nanotubes are mixed in a weight ratio of 3:2.
[0097] The mass ratio of component A to component B is 100:10.
[0098] The preparation of the conductive coating comprises the following steps: Step 1: blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent under ultrasonic dispersion and high-speed stirring conditions to prepare a stable carbon nanotube / graphene conductive slurry; wherein the modification step of the dispersant is the same as that of Example 3; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare a stable component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1 hour until the scraper fineness is controlled within 25µm; Step 3: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0099] Comparative Example 9 This embodiment provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 2 parts of iron red, 0.5 parts of phthalocyanine blue, 1.45 parts of carbon nanotube / graphene conductive paste, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-6026F, 1.5 parts of leveling agent BYK-361N, 2 parts of drying agent dibutyltin dilaurate, 16.55 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 23 parts of xylene, 3 parts of butyl acetate, 5 parts of diformate).
[0100] The carbon nanotube / graphene conductive slurry is composed of the following components: 0.15 parts of graphene, 0.1 parts of carbon nanotubes, 0.3 parts of modified polymer dispersant Anti-Terra-203, 0.4 parts of positioning agent butyl acetate cellulose, and 0.5 parts of a third diluent (0.8 parts of cyclohexanone, 2.5 parts of butyl acetate, and 1 part of diformate); wherein the graphene and the carbon nanotubes are mixed in a weight ratio of 3:2.
[0101] The mass ratio of component A to component B is 100:10.
[0102] Step 1: blending the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent under ultrasonic dispersion and high-speed stirring conditions to prepare a stable carbon nanotube / graphene conductive slurry; wherein the modification step of the dispersant is the same as that of Example 3; Step 2: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare component A; wherein, in step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; ultrasonic dispersion is performed for 30 minutes, and the temperature is controlled within 30°C during the entire ultrasonic dispersion process, and the speed of high-speed stirring is controlled at 1200 rad / min; in step 2, the blended mixture is ground for 1.5 hours until the scraper fineness is controlled within 25µm to obtain component A; Step 3: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0103] Comparative Example 10 This embodiment provides a conductive coating and a preparation method thereof, wherein the conductive coating is composed of the following components in parts by weight: Component A: 38 parts of fluorocarbon resin JF-2X, 12 parts of talc (1250 mesh), 5 parts of precipitated barium sulfate, 3 parts of light calcium carbonate, 14 parts of titanium dioxide, 2 parts of iron red, 0.5 parts of phthalocyanine blue, 0.15 parts of graphene, 0.1 parts of carbon nanotubes, 2 parts of matting powder ED-30, 2 parts of adhesion promoter EDL-6026F, 1.5 parts of leveling agent BYK-361N, 2 parts of drying agent dibutyltin dilaurate, 17.75 parts of the first diluent (1.5 parts of cyclohexanone, 15 parts of xylene) Component B: 10 parts of isocyanate curing agent N3390, Component C: 23 parts of the second diluent (1.5 parts of cyclohexanone, 2 parts of propylene glycol methyl ether acetate, 23 parts of xylene, 3 parts of butyl acetate, 5 parts of diformate).
[0104] The mass ratio of component A to component B is 100:10.
[0105] Step 1: Under ultrasonic dispersion and high-speed stirring conditions, carbon nanotubes, graphene, fluorocarbon resin, filler, pigment, additive, matting powder and the first diluent are blended to prepare component A; wherein the ultrasonic dispersion is performed using an ultrasonic disperser, and the power of the ultrasonic disperser is 800W; the ultrasonic dispersion is performed for 30 minutes, the temperature is controlled within 30°C during the entire ultrasonic dispersion process, the speed of high-speed stirring is controlled at 1200 rad / min, and the blended mixture is ground for 1.5 hours until the scraper fineness is controlled within 25µm, thereby obtaining component A; Step 2: Add the isocyanate curing agent (component B) and the second diluent (component C) to component A, stir for half an hour, and obtain a conductive coating.
[0106] test (1) The conductive coatings prepared in Examples 1-3 and Comparative Examples 1-10 were tested. The test standards are shown in Table 1, and the test results are shown in Table 2.
[0107] Table 1
[0108] Table 2
[0109] (2) Example 2, Comparative Example 6 and Comparative Example 8 respectively used modified polymer dispersants, modified amine salt ionic dispersants and modified controlled free radical dispersants to prepare carbon nanotube / graphene conductive slurries. After dispersion by ultrasonic and high-speed stirring process, the dispersion degree of conductive powder in the system and the stability of the dispersion were tested to evaluate the dispersion effect of different dispersants. The experimental results are shown in Table 3 and Figure 1-2 .
[0110] Table 3 Dispersant applicability test results
[0111] According to Table 3 and Figure 1-2 It can be seen that in the experimental group using modified polymer dispersant, the degree of particle flocculation in the paint slurry was the smallest after 30 days of hot storage, the dispersion effect was the best, and the storage stability was better than the other two groups.
[0112] in conclusion: Compared with Example 1 and Comparative Example 1, the coatings differ in that no carbon nanotubes are added in Comparative Example 1. Compared with Example 1 and Comparative Example 1, the surface resistance of the carbon nanotube / graphene composite is much lower than that of graphene alone.
[0113] Compared with Example 1 and Comparative Example 2, the difference in the coating is that no graphene is added in Comparative Example 2. Compared with Example 1 and Comparative Example 2, the surface resistance value of Example 1 is much lower than that of Comparative Example 2.
[0114] Compared with Example 1 and Comparative Example 3, the difference in the coating is that Comparative Example 3 does not use ultrasound or high-speed stirring to disperse the carbon nanotubes / graphene in advance. Compared with Example 1 and Comparative Example 3, the advance dispersion treatment of the carbon nanotubes / graphene will reduce the surface resistance of the coating, improve the overall performance of the coating, and affect the storage stability of the coating.
[0115] Compared with Example 2 and Comparative Example 4, the difference in the coating is that the carbon nanotube / graphene ratio in Comparative Example 4 is changed to 1:1. Compared with Example 2 and Comparative Example 5, the difference in the coating is that the carbon nanotube / graphene ratio in Comparative Example 5 is changed to 3:2. Compared with Example 2, the addition ratio of graphene and carbon nanotubes in Comparative Examples 4 and 5 is changed, which affects the conductive properties of the coating.
[0116] Compared with Example 2 and Comparative Example 6, the coatings differ in that the modified polymer dispersant Anti-Terra-203 is replaced with a modified amine salt ionic dispersant sn-5027 in Comparative Example 6. Compared with Example 2 and Comparative Example 6, the dispersion effect of sn-5027 is poor, resulting in high surface resistance, increased average particle size after 30 days of thermal storage, and poor storage stability of the coating.
[0117] Compared with Example 3 and Comparative Example 7, Comparative Example 7 does not add carbon nanotubes / graphene, but replaces it with nano antimony-doped tin dioxide. Compared with Example 3 and Comparative Example 7, the coating prepared in Comparative Example 7 improves the adhesion of the system, but the adhesion by the pull-off method cannot meet the requirement of 15MPa.
[0118] Compared with Example 3 and Comparative Example 8, the modified polymer dispersant in Comparative Example 8 is replaced with the modified controlled radical dispersant DISUPER S9100. Compared with Example 3 and Comparative Example 8, the dispersion effect is worsened, the surface resistance value is increased, and the storage stability of the coating is poor.
[0119] Compared with Example 3 and Comparative Example 9, the content of the carbon nanotube / graphene composite in Comparative Example 9 is not in the range of 7-16%, the content of graphene and carbon nanotubes in the slurry system is too high, the slurry viscosity is too high, and the interaction between the fluorocarbon resin and the carbon nanotube / graphene is greatly weakened, which is not conducive to dispersion, grinding and storage, and will also affect the surface resistance value of the coating.
[0120] Compared with Example 3 and Comparative Example 10, in Comparative Example 10, carbon nanotubes and graphene are directly added to component A without preparing a conductive paste. Compared with Example 3, the surface resistance is larger, and the pulling method cannot meet the requirement of 15 MPa.
[0121] The above is a detailed introduction to a highly storage-stable conductive coating and a preparation method thereof provided by the present application. For ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the present application.
[0122] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A conductive coating, characterized in that: The conductive coating is composed of component A, component B and component C. In terms of weight, the component A is 100 parts, the component B is 8-12 parts, and the component C is 10-25 parts; Wherein, in parts by weight, the component A includes: 20-45 parts of fluorocarbon resin, 10-30 parts of filler, 5-17 parts of pigment, 3-7 parts of carbon nanotube / graphene conductive paste, 2-6 parts of auxiliary agent, 10-20 parts of first diluent and 1-2 parts of matting powder; Component B: 8-12 parts of curing agent, Component C: 10-25 parts of the second diluent, The carbon nanotube / graphene conductive paste is composed of the following components by weight: 0.15-0.6 parts of graphene, 0.1-0.6 parts of carbon nanotubes, 0.4-0.7 parts of positioning agent, 0.3-0.8 parts of modified dispersant and 2.5-4 parts of third diluent, wherein the weight ratio of graphene to carbon nanotubes is 3:2; In the carbon nanotube / graphene conductive paste, the weight ratio of the carbon nanotube / graphene composite in the carbon nanotube / graphene conductive paste is 7-16%; the modified dispersant is a dispersant modified by a modified compound.
2. The conductive coating according to claim 1, characterized in that: In the carbon nanotube / graphene conductive slurry, the positioning agent is a cellulose ester positioning agent; The modified dispersant is a polymer dispersant modified by a modified compound.
3. The conductive coating according to claim 2, characterized in that: The positioning agent is butyl acetate cellulose; The modified compound is imidazole or polyethylene glycol; The molar ratio of the active group of the dispersant to the modified compound is 1:1 to 1:
2.
4. The conductive coating according to any one of claims 1 to 3, characterized in that: The fluorocarbon resin is chlorotrifluoroethylene-vinyl ester resin; The filler is an inorganic filler, selected from at least one of talcum powder, precipitated barium sulfate, and light calcium carbonate; The pigment is at least one of an organic pigment and an inorganic pigment; The auxiliary agent is at least one of a leveling agent, a drying agent and an adhesion promoter.
5. The conductive coating according to any one of claims 1 to 3, characterized in that: The curing agent is isocyanate.
6. The conductive coating according to claim 5, characterized in that: The curing agent is aliphatic polyisocyanate.
7. The conductive coating according to claim 6, characterized in that: The curing agent is hexamethylene diisocyanate.
8. The conductive coating according to any one of claims 1 to 3, characterized in that: The first diluent, the second diluent and the third diluent respectively include at least one of cyclohexanone, propylene glycol methyl ether acetate, xylene, butyl acetate and dibasic acid ester; The compositions of the first diluent, the second diluent and the third diluent are the same or different.
9. A method for preparing the conductive coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Under ultrasonic dispersion and high-speed stirring conditions, the carbon nanotube / graphene composite, the modified dispersant, the positioning agent, and the third diluent are blended to prepare a carbon nanotube / graphene conductive slurry; Step 2: blending the carbon nanotube / graphene conductive slurry, fluorocarbon resin, filler, pigment, additive, first diluent and matting powder under ultrasonic dispersion and high-speed stirring conditions, and grinding the blended mixture to obtain component A; Step 3: Add the curing agent of component B and the second diluent of component C into component A, and stir to obtain the conductive coating.
10. The method according to claim 9, characterized in that Step 1 also includes a modification treatment of the dispersant: dissolving the dispersant with a solvent, adding the modified compound and stirring until it is completely dissolved; heating the reaction system and reacting under nitrogen protection; after the reaction is completed, removing the solvent to obtain a modified dispersant; wherein, The solvent is tetrahydrofuran; The molar ratio of the active group of the dispersant to the modified compound is 1:1 to 1:2; The heating temperature is 60-80°C; The reaction time is 6-10h.
11. The method according to claim 9 or 10, characterized in that: In step 1 and step 2, ultrasonic dispersion is performed using an ultrasonic disperser; The power of the ultrasonic disperser is 800W; The ultrasonic dispersion time is 5-30min; The slurry temperature does not exceed 30°C during ultrasonic dispersion; The speed of high-speed stirring is 1000 rad / min - 1200 rad / min; The high-speed stirring time is 1-3h.
12. The method according to claim 9 or 10, characterized in that: In step 2, the blended mixture is ground to a fineness within 25 μm; The grinding time is 1-2h.
13. The method according to claim 9 or 10, characterized in that: In step 3, the stirring time is 0.2-1h.
14. The method according to claim 13, characterized in that The stirring time is 0.5h.
15. A conductive coating prepared by the method according to any one of claims 9 to 14.
16. Use of the conductive coating according to any one of claims 1 to 8 or the conductive coating according to claim 15 on an aircraft surface; the conductive coating is used as a primer or a topcoat.
17. A coating formed from the conductive paint according to any one of claims 1 to 8 or the conductive paint according to claim 15, wherein the coating is formed by applying the conductive paint onto a substrate and curing the coating.
Citation Information
Patent Citations
Static conductive coating containing carbon nanotubes and preparation method thereof
CN116023846A
Graphene static conductive coating and preparation method thereof
CN116731593A
Modified white graphene composite anticorrosive paint and preparing method thereof
CN106243943A
Graphene conductive slurry as well as preparation method and application method of graphene conductive slurry
CN107298924A
Water-based fluorocarbon resin heavy anti-corrosion coating and preparation method thereof
CN112745723A
Cited By
Modified conductive coating with high chemical resistance and preparation method thereof
CN122127863A